War, conflict and human rights theory and practice - Sriram, Chandra Lekha; Martin-Ortega, Olga; Herman, Johanna (Routledge, Taylor & Francis Group, 2018)
War, Conflict and Human Rights is an innovative inter-disciplinary textbook, combining aspects of law, politics and conflict analysis to examine the relationship between human rights and armed conflict. This volume will be essential reading for students of war and conflict studies, human rights and international humanitarian law, and highly recommended for students of conflict resolution, peacebuilding, international security, transitional justice and international relations generally.